A Case Study of Students’ Anxiety in Speaking English And How They Cope The Feeling - Triana, Desinta; Suharjito, Bambang; Rofiq, Annur (English Education Study Program, 2021)
This study analyzes the factors of the students’ anxiety in speaking English and also explores the strategies used by the students to cope with their anxiety. The three participants of this study were selected from 36 students of X TKJ 1 in SMKN 2 Jember that experienced speaking anxiety as illustrated by Oxford. This study applied qualitative and quantitative case study design. Classroom observation was done four times to select the participants. The results of questionnaire and interview were analysed by using Miles and Hubberman’s model. The findings showed that the students in the English speaking class experienced excessive fear and anxiety. There were 2 participants who exhibited test anxiety and the other one exhibited communication apprehension. Their strategies to overcame the anxiety were; avoiding eye contact, relaxation, and asking for teachers’ help.